Penentuan Strategi Pegembangan UKM Tempe Pak Fadli Menggunakan Metode Analisis SWOT dan Boston Consulting Group (BCG) - Wiss Al Qorni; Misbach Munir (MES Bogor, 2024)
Micro, small, and medium enterprises (MSMEs) are an important part of the Indonesian economy to improve people's welfare. Pak Fadli's Tempe UKM located in Parerejo Village, Purwodadi District, faces the problem of fierce competition in the tempeh industry and the lack of information obtained by business actors regarding modern technology in the marketing system. Using SWOT Analysis and BCG Matrix, this study aims to find out internal and external factors and what strategies can be used for the growth of Mr. Fadli's tempe business. The results showed using a SWOT Analysis that Pak Fadli's Tempe SMEs had a higher total strength score (4.08) than a total weakness score (3.17), which placed him in Quadrant I. This shows that Pak Fadli's Tempe SMEs should use all their strengths to take advantage of the best opportunities. According to Matrix BCG's calculations, Pak Fadli's Tempe SMEs are in Quadrant III (Cash Cows) with a total market share value of 1.03 and a market growth value of 2.4%. Because it has a large market share but is in a slow-growing sector. Increasing market share and expanding distribution networks is one strategy that can be used. With this research, it is hoped that it can provide recommendations for development strategies and the right marketing strategy for Pak Fadli Tempe SMEs to be able to compete with their competitors.